Red Dwarf. IV [videorecording (DVD)] - Grant, Rob (Robert Ray); Naylor, Doug; Bye, Ed; Barrie, Chris, 1960-; Charles, Craig, 1964-; John-Jules, Danny; Llewellyn, Robert, 1956-; Hayridge, Hattie (Warner Home Video, 2004)
Ace Rimmer arrives from an alternate dimension, Kryten falls in love and Lister's curry tries to kill him in six more slices of classic Red Dwarf chaos.